AGAINST ALL ODDS: REFLECTIONS ON VIOLENCE AND CIVILITY THROUGH PERSONAL NARRATIVES OF UKRAINIAN STUDENTS. - Lukenchuk, Antonina (Journal of Ethnographic & Qualitative Research)
The purpose of the present study was to understand, through personal narratives, the experiences of Ukrainian university students who participated in the 2013-2014 Maidan revolutionary events and to juxtapose their narratives with the theoretical discourses on violence and civility drawn from the works of several contemporary Western thinkers. The data analysis resulted in the identification of five interrelated themes: "If Not Me, Then Who? If Not Now, Then When?" The Participants' Motivation for Activism; Violence Contextualized within the Maidan Events; Ukraine vs. Russia: A "Hybrid" War; Civility as an Antidote to Violence; and Big Hopes and Dreams for Ukraine. The results of the present study convey the participants' stories of bravery, dedication to the cause worthy of pursuit, and the belief in one's ability to engender societal change. The findings of the present study provide important implications for the scholarship on violence, just war theory, and civility.